2022
DOI: 10.3390/cancers14061564
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Thymic Epithelial Tumors Hints to a Strong Warburg Effect, Glutaminolysis and Precarious Redox Homeostasis as Potential Therapeutic Targets

Abstract: Thymomas and thymic carcinomas (TC) are malignant thymic epithelial tumors (TETs) with poor outcome, if non-resectable. Metabolic signatures of TETs have not yet been studied and may offer new therapeutic options. Metabolic profiles of snap-frozen thymomas (WHO types A, AB, B1, B2, B3, n = 12) and TCs (n = 3) were determined by high resolution magic angle spinning 1H nuclear magnetic resonance (HRMAS 1H-NMR) spectroscopy. Metabolite-based prediction of active KEGG metabolic pathways was achieved with MetPA. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 83 publications
3
21
0
Order By: Relevance
“…Lactic acid is a byproduct of glycolysis and it can promote tumor progression 41 . Tissue lactic acid was reported to have higher levels in aggressive (B2, B3 and TC) compared with indolent TETs and normal thymic, suggesting a strong “Warburg effect” as potential vulnerabilities in thymoma development and progression 5 . Another sequela of the metabolic program Warburg effect is the acidification of the tumor microenvironment, which is a key factor in cancer somatic evolution and progression to malignancy 42 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lactic acid is a byproduct of glycolysis and it can promote tumor progression 41 . Tissue lactic acid was reported to have higher levels in aggressive (B2, B3 and TC) compared with indolent TETs and normal thymic, suggesting a strong “Warburg effect” as potential vulnerabilities in thymoma development and progression 5 . Another sequela of the metabolic program Warburg effect is the acidification of the tumor microenvironment, which is a key factor in cancer somatic evolution and progression to malignancy 42 .…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, it is hard to achieve accurate pre‐operative diagnosis of thymoma by only imaging and new objective and reliable biomarkers are needed 9 . For those patients with unresectable disease or those who progress after surgery and radiotherapy, the current treatment strategy is platinum‐based chemotherapy; however, no standard treatments are clinically implemented if patients are resistant to platinum‐based therapies 3,5 . Immune checkpoint inhibitors such as PD‐1 and PD‐L1 inhibitors represent one of the new targeted therapeutic strategies; however, these may induce severe autoimmune adverse reactions in thymoma patients 5 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was only a single study of metabolomic analysis in TETs by nuclear magnetic resonance spectroscopy, which included tissue samples from 15 TETs and 4 normal controls. It was suggested that pathways associated with cysteine, glutathione, lactate, and glutamine appear to be promising therapeutic targets based on metabolite differences between thymic epithelial tumor tissue and normal thymic tissue proline [25]. Inhibitors of glutaminolysis and the downstream tricarboxylic acid cycle (TCA) are also expected to be reasonable therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%